2016
DOI: 10.1186/s12938-016-0266-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of simultaneously measured four-limb blood pressures with cardiovascular function: a cross-sectional study

Abstract: BackgroundSimultaneous measurement of four-limb blood pressures can improve the accuracy of cardiovascular disease diagnosis. This study aims to investigate the association of simultaneously measured four-limb blood pressures with cardiovascular function as the non-invasive diagnostic method of cardiovascular disease in primary care.Methods229 subjects (62 males, mean age, 63.50 ± 11.13 years; 167 females, mean age, 59.47 ± 7.33 years) were enrolled. Four-limb blood pressure measurements were simultaneously pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The original pulse wave data were from the “Study on Evaluation Method of Cardiovascular System Based on Non-invasive Detection of Blood Pressure and Pulse-Wave of Limbs 29 ”, which recruited 412 subjects and determined their physiological parameters and more than 12,000 cycles of pulse waves. The pulse and blood pressure signal measuring device was Fukuda VS-1500A.…”
Section: Methodsmentioning
confidence: 99%
“…The original pulse wave data were from the “Study on Evaluation Method of Cardiovascular System Based on Non-invasive Detection of Blood Pressure and Pulse-Wave of Limbs 29 ”, which recruited 412 subjects and determined their physiological parameters and more than 12,000 cycles of pulse waves. The pulse and blood pressure signal measuring device was Fukuda VS-1500A.…”
Section: Methodsmentioning
confidence: 99%
“…The study, its experimental protocols, and relevant details were approved by the Institutional Ethics Committee of Beijing University of Technology. This study was a retrospective analysis of the “Study on Evaluation Method of Cardiovascular Disease Based on Non-invasive Detection of Blood Pressure and Pulse-Wave of Limbs” ( Song et al, 2016 ), which recruited 412 subjects, where the clinic data collection as shown in Figure 1A . Herein, the Fukuda VS-1500A, manufactured by Beijing Fukuda Electronic Medical Instrument Co., Ltd, obtained the pulse waveform of four limbs, synchronously measures the blood pressure of four limbs, and automatically calculates the pulse wave velocity, ankle-brachial index, cardio-ankle vascular index, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, this presents a large gap in treating CVDs. Studies have shown that cardiovascular functions are characterized by pulse waves changes in hemodynamic diagnosis indexes (HDIs) are reflected by changes in pulse waveforms, which can be used for the early detection of CVDs symptoms (Chow et al, 2008;O'Rourke, 2009;Celermajer et al, 2012;SONG and QIAO, 2015;Wang et al, 2022). HDIs can be used to comprehensively evaluate the health status of a patient's CVS, particularly for patients older than 50 years and prone to CVDs, more accurately and directly in terms of total peripheral resistance (TPR), stroke volume (SV), arterial compliance (AC), etc., (Thenappan et al, 2015;Suzuki et al, 2019;Trammel and Sapra, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This estimating method has been described in our previous study (Li et al, 2020). The brachial artery pressure was collected using a Fukuda pulse wave meter (Song et al, 2016), whereas the CO data were monitored using a color Doppler ultrasound. We performed numerical simulations of the different…”
Section: Verification By Clinical Experimentsmentioning
confidence: 99%